Customers’ loyalty profiles - Bartosik-Purgat, Małgorzata (Economics and Business Review, 2007)
Brand consumer loyalty is one of the most important issue in the area of consumer behaviour. Companies conduct many researches to find out the needs and preferences of potential buyers because satisfied and happy consumers usually come back and buy products of the same companies or brands. This is only one aspect of consumer loyalty, another one is telling other consumers about the product and brand and encouraging them to buy the product of a particular brand. The article presents results of empirical researches conducted among Polish consumers about their brand loyalty. These results help to construct the loyalty profile of a Polish consumer. (original abstract)